Postoperative pyoderma gangrenosum: A rare complication after appendectomy - Faghihi, G (J Postgrad Med, 2015)
Pyoderma gangrenosum (PG) is an uncommon inflammatory ulcerative skin disease. It is characterized by painful progressive necrosis of the wound margins. Rarely, postoperative pyoderma gangrenosum (PPG) manifests as a severe disturbance of wound healing following surgical interventions. Only rare cases of this complication have been reported after appendectomy. We report a case of PPG in a 29-year-old female after appendectomy. She was successfully treated with oral prednisolone. Postoperative pyoderma gangrenosum should be kept in mind in the differential diagnosis of any postoperative delayed wound healing, because this disease is simply distinguished from a postoperative wound.